التربیة بالتسلیم لله تعالى وآثارها فی حیاة المسلم - صالح، نهیل على حسن; المهیدات، تسنیم نورالدین فالح (جامعة الأزهر - كلية الشريعة والقانون بتفهنا الأشراف - دقهلية, 2018)
This research aims to study and clarify the most important principle of the Islamic principles, which is the faith and Surrender to God. and this subject has a huge positive impact on us as individuals and also on the surrounding society. also, this very important principle represents a sort of immunity which protects a Muslim brain and perspectives. So this study will clarify how to translate the trust in god into an effective rules to follow in our daily basis. Raising the individual Muslim to trust and have the faith in god means understanding the Islamic reference and not only that, but letting this understanding alive through following it in his daily routine, that doesn’t necessarily means to stop his mental instinctive functions, but making it effective in understanding the Islamic versions. And it directs to the right destination. It also proved the necessity of defining the needed rules to guarantee the effectiveness of this important principle in the Muslim’s life. reaching the results which created the individual’s positive personality and other surroundings. On the other hand, this research recommends the necessity of teaching the new generations this important principle. Which completes the politeness and appreciation in a Muslim’s relationship with god. And a proof for his love. In addition to teach them -the new generation- the skills of critical thinking. Which differentiates between following the habits of the present culture and quoting or copying the beneficial traditions and principles of the old cultures and being proud of their religion and beliefs. And by taking the responsibility of serious directing and insulation to build strong united community.
هدف البحث إلى دراسة أصل عظيم ومبدأ أساسي من مبادئ التربية الإسلامية وهو التربية بالتسليم لله تعالى، لما لهذا الموضوع من أثر ايجابي في حياة الفرد والمجتمع، حيث يمثل هذا النوع من التربية الحصانة الفكرية والمناعة الواقية للعقل المسلم، فكان البحث لتأصيل التربية بالتسليم لله، وبيان التطبيقات العملية لها، وتحديد أهم القواعد الضابطة لتفعيلها في حياة المسلم. وخلص البحث إلى أن التربية بالتسليم لله تعالى تعني تنشئة الفرد المسلم على فهم المرجعية الشرعية ومقاصدها وتقديمها وتفعيلها في شؤونه كلها، وذلك بالانقياد والطاعة والرضا، وهذا لا يعني تعطيل العقل، وإنما تفعيله في فهم النصوص الشرعية، وتوجيهه الوجهة الصحيحة، كما أثبت الدراسة ضرورة تحديد القواعد اللازمة لضمان فاعلية هذه التربية في حياة المسلم، وصولاً إلى الآثار التربوية التي شكلت شخصية الفرد الإيجابية وشخصية الأمة الفاعلة. ويوصي البحث بضرورة تعليم الأبناء مبدأ التسليم، الذي هو من كمال الأدب مع الله تعالى، ودليل على محبته، بالإضافة إلى تعليمهم مهارات التفكير الناقد؛ بحيث يميزون بين التبعية الثقافية وبين الاقتباس النافع، مع تقديمهم أولوية الاعتزاز بالدين والعقيدة، كما توصي الدراسة بأن يعتني المربون بتعظيم الوحيين عن طريق التوجيه التربوي الجاد للمناهج التعليمية.
Keywords: التربية الاسلامية -- القيم التربوية -- المرجعية الشرعية -- تربية الأبناء